COMPARATIVE ANALYSIS OF THE TAX BURDEN ON FARMS UNDER THE GENERAL AND SIMPLIFIED TAXATION SYSTEMS IN UKRAINE - YEREMIAN, Olena; MYKHAILOVYCH, Olesia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article provides a comprehensive comparative analysis of the tax burden on farm households (FHs) in Ukraine under the general taxation system and the simplified system (Group 4 single tax). The research addresses a highly relevant issue, as the agrarian sector generates nearly 10% of Ukraine's GDP and over 40% of export revenues (2024 data). The efficiency of taxation directly influences the financial sustainability of farm enterprises, their capacity for expansion, and competitiveness in both domestic and international markets.The study investigates the advantages and limitations of both regimes for limited liability companies (LLCs) with hired labor and family-based farms, considering operational scale, resource availability, and strategic objectives. The general taxation system imposes multiple obligations, including an 18% corporate profit tax, value-added tax (20%, 14%, or 7% depending on product type), land tax, a 22% single social contribution (SSC), an 18% personal income tax (PIT), and, starting in 2025, a 5% military levy introduced by Law №4113-IX. This framework favors export-oriented LLCs but requires high administrative capacity and entails significant compliance costs.In contrast, the simplified system applies a fixed tax rate ranging from 0.95% to 2.43% of the normative monetary valuation per hectare. It exempts taxpayers from most other taxes, thus reducing the compliance burden and ensuring predictability for family farms with limited resources. However, it restricts diversification of activities beyond agricultural production, thereby limiting innovation and broader market integration.Methodologically, the research relies on systemic and comparative analysis combined with content analysis of regulatory acts, including the Tax Code of Ukraine and the Law “On Farms.” Legislative changes adopted in 2023–2025, such as the minimum tax obligation (MTO) and differentiated VAT rates, are incorporated into the analysis. Statistical data from the State Tax Service of Ukraine and scholarly publications serve as the empirical basis. Comparative tables illustrate key differences in tax structures between systems.The findings demonstrate that the general taxation system supports scalability and global market participation, whereas the simplified system ensures stability and lower risks for smaller farms. Nevertheless, the simplified regime’s narrow scope regarding eligible activities and land area constrains long-term growth.Practical recommendations emphasize the importance of strategic tax planning under conditions of martial law, rising resource costs, and ongoing European integration. Particular attention should be devoted to consultations with tax authorities on MTO assessments and VAT registration, which have substantial implications for economic efficiency.The study concludes that balancing efficiency, fairness, and competitiveness is essential for optimizing agricultural taxation in Ukraine. Future research should focus on aligning national tax policies with EU standards to strengthen the investment attractiveness, resilience, and competitiveness of the agrarian sector.
Keywords: tax burden; farms (FG); taxation system; single tax (group 4); minimum tax liability (MTL); family farm; limited liability company; agricultural sector